Fiscal Deficit and Public Debt in the Western Balkans : 15 Years of Economic Transition - Koczan, Zsoka (IMF Working Papers; Working Paper, 2015)
In this paper we analyze how Western Balkans public finances adapted to the boom-bust cycle. Large capital inflows into emerging European economies during the mid-2000s resulted in rapid economic growth and convergence to EU income levels. This also resulted in improved fiscal positions of most countries, on the back of strong revenue performance. Yet, since the onset of the global economic crisis, many countries have struggled to adjust to the new situation of lower external financing and lower growth.